PENIS GROWTH RESPONSE TO HORMONAL THERAPY IN CHILDREN WITH MICROPENIS AT HASAN SADIKIN HOSPITAL - Gandakusuma, Evan; Sibarani, Jupiter (Indonesian Urological Association, 2023)
Objective: This study aims to determine the response of penis growth to testosterone injection. Material & Methods: The study was conducted on all cases of micropenis from January 2016 to December 2020. Each subject who met the criteria for micropenis received 25 mg of intramuscular testosterone ester injection, in 4 doses with an interval of 1 week. Evaluation is done at the beginning, before administration of testosterone, then an evaluation is carried out for each patient before testosterone injection until 1 week after the 4th injection. Penis measurement is done by fully stretched length measurement. Results: There were 62 patients who met the criteria for micropenis. The average age of patients with micropenis when they first came was 5.9 years. The patient's mean initial penile length was 2.13 cm. There was an increase in penis length of 32% in the first injection, 28% after the second injection, 18% after the third injection and 14% after the fourth injection. The average length of the penis at the first, second, third and fourth injections was 2.53 cm, 3.24 cm, 3.65 cm and 4.01 cm, respectively. At the end of treatment, there was an average increase in penile length of 75.8% compared to the beginning of treatment. Conclusion: In conclusion, it can be said that testosterone therapy in micropenis patients gave a good response in terms of increasing penile length by 75.8% and increasing the average from 2.13 cm to 4.01 cm.